Global Trade Watch : Trade Developments in 2015 - Constantinescu, Cristina; Mattoo, Aaditya; Ruta, Michele (World Bank, Washington, DC, 2016)
After sharply declining in the first half of 2015, world trade began to grow, albeit at a slow pace. Preliminary data indicate that merchandise import growth was 1.7 percent in 2015, down from 3 percent in 2014. Recent trade developments should be seen in the context of a deceleration in trade growth since the early 2000s, and particularly since the global financial crisis. These developments reflected a combination of old and new cyclical factors as well as enduring structural determinants, such as the maturation of global value chains and the slower pace of trade liberalization. In particular, trade developments in Latin America and Eastern Europe and Central Asia mostly reflected lower imports of recession hit commodity exporters such as Brazil and Russia. Latin America contributed 6 percent to the downward pull in global imports in 2015. Except for Japan, imports and exports of advanced economies did not show signs of a significant downturn, but were sluggish. Lower commodity prices have reduced real incomes in commodity producers and led to a contraction in their imports from all regions, including China. At the same time, the gradual shift from investment to consumption in China, and the more significant contraction in its industrial production seen in early 2015, have reduced its imports from other regions, including commodity producers.